2015
DOI: 10.1557/opl.2015.329
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Nanostructured Thermoelectric Materials and Devices

Abstract: We present results of modeling and experimental characterization of thermoelectric (TE) materials built on new fabrication principles, involving the coating of three-dimensionally structured quantum well super-lattice substrates with PbTe/PbSe. A new system for wafer-scale electrochemical deposition of such structures was specifically developed and will be described in this paper. Scanning electron microscopy (SEM) was used to measure film thickness and electron diffraction spectroscopy (EDS) was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…21 For the Seebeck coefficient measurements in the direction vertical to the surface, our collaborator in MicroXact Inc. reported similar results that the PbTe/PbSe nanolaminate structure grown on micro-porous silicon membranes exhibits higher Seebeck coefficients (78670 ± 15540 μV/K) compared with the thermoelectric nanolaminate structure grown on a planar bulk silicon wafer (250 ± 27 μV/K). 22 This porous Si membrane is fabricated by removing the Si from the back side with KOH etching until the pores are reached from the back side. From the results of our Seebeck measurements in both the horizontal and vertical directions, the low dimensional ALD nanolaminate structures synthesized inside the pores of porous silicon membranes exhibit higher Seebeck coefficients than previously reported values.…”
Section: Resultsmentioning
confidence: 99%
“…21 For the Seebeck coefficient measurements in the direction vertical to the surface, our collaborator in MicroXact Inc. reported similar results that the PbTe/PbSe nanolaminate structure grown on micro-porous silicon membranes exhibits higher Seebeck coefficients (78670 ± 15540 μV/K) compared with the thermoelectric nanolaminate structure grown on a planar bulk silicon wafer (250 ± 27 μV/K). 22 This porous Si membrane is fabricated by removing the Si from the back side with KOH etching until the pores are reached from the back side. From the results of our Seebeck measurements in both the horizontal and vertical directions, the low dimensional ALD nanolaminate structures synthesized inside the pores of porous silicon membranes exhibit higher Seebeck coefficients than previously reported values.…”
Section: Resultsmentioning
confidence: 99%
“…However, our non-doped PbTe and PbSe films evidently have a lower carrier concentration than the doped films in the literature, which consequently results in the onset of intrinsic conduction at a lower temperature [75]. For the Seebeck coefficient measurements in the direction vertical to the surface, our collaborator at MicroXact, Inc. measured similar trends and found that the PbTe/PbSe nanolaminate structure grown on round-shaped porous silicon membranes exhibits even higher absolute Seebeck coefficients, with values of 78670 ± 15540 µ V/K in the vertical direction, compared with the thermoelectric nanolaminate structure grown on a planar bulk silicon wafer (250 ± 27 µ V/K), shown as Figure S2 in the supplementary materials [68].…”
Section: Lead Chalcogenide Based Ald Nanolaminate On Porous Templatesmentioning
confidence: 76%
“…Both bulk alloy compound and nanostructured PbTe/PbSe have been investigated over the decades. Nanostructured PbTe/PbSe film can be deposited by MBE [8,48] and E-ALD [68,69]. To the best of our knowledge, vacuum based thermal ALD technology was first applied for the synthesis of PbTe/PbSe nanolaminate structures in our work [1,70].…”
Section: Lead Chalcogenide Based Ald Nanolaminate On Porous Templatesmentioning
confidence: 99%
See 1 more Smart Citation